2013
DOI: 10.1063/1.4788741
|View full text |Cite
|
Sign up to set email alerts
|

Growth and stability of zinc blende MgS on GaAs, GaP, and InP substrates

Abstract: The molecular beam epitaxial growth of zinc blende (ZB) MgS on GaAs, GaP, and InP substrates has been investigated by X-ray diffraction and RHEED, with MgS layer strain varying between 3.1% compressive strain (GaP) and 4.4% tensile strain (InP). ZB MgS could be grown on all three substrates. X-ray diffraction showed substantial MgS relaxation during growth before conversion to the rock salt phase. Results are compared with predictions that stable growth on GaP is unlikely and relaxed ZB MgS does not grow in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Polymorph stabilization has been previously observed for metastable ZB-MgS films deposited on GaAs crystals [32], and for various metastable oxides and nitrides [8,12] grown on single-crystal substrates, up to a small critical thickness, using complex MBE methods. The important differences between this study and all of these prior thinfilm reports are stabilization of high-energy polymorphs in materials systems, where lattice-matched single-crystal substrates are not available, complex deposition methods are not feasible, and thick films are required for practical applications.…”
Section: B Stabilization Mechanismmentioning
confidence: 83%
“…Polymorph stabilization has been previously observed for metastable ZB-MgS films deposited on GaAs crystals [32], and for various metastable oxides and nitrides [8,12] grown on single-crystal substrates, up to a small critical thickness, using complex MBE methods. The important differences between this study and all of these prior thinfilm reports are stabilization of high-energy polymorphs in materials systems, where lattice-matched single-crystal substrates are not available, complex deposition methods are not feasible, and thick films are required for practical applications.…”
Section: B Stabilization Mechanismmentioning
confidence: 83%
“…Using this process, we demonstrated ELO of ZnSe/ZnCdSe quantum well structures from GaAs substrates. 7 Recently, we have successfully grown heterostructures containing ZB MgS on three different III-V substrates: GaP, GaAs, and InP, 8 where the MgS layer has strains ranging from 4.4% (tensile) on InP to À3.0% (compressive) on GaP. In this paper, we demonstrate that ZB MgS can be used as a sacrificial layer in ELO for II-VI heterostructures deposited on all three substrates.…”
Section: Introductionmentioning
confidence: 67%
“…Significantly, there is no miscibility gap in the ternary ZnMgS system and in this case much larger interdiffusion would be expected leading to a substantially smaller d, and we have recently observed MgS/ZnS intermixing in double crystal X-ray spectra from thin ZnS/MgS/ZnS heterostructures. 8 A full calculated phase diagram for CdMgSSe has not been published, but using the same model as used previously for ZnMgSSe, 14 it is found that the region of miscibility is drastically reduced to the percent level. CdSe and MgS are effectively immiscible, giving sharp boundaries between layers and a larger d for the same amount of deposited material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most stable known selenide of rhenium is the layered transition metal dichalcogenide ReSe 2 but it is likely to be possible to obtain metastable zincblende ReSe layers by non‐equilibrium growth techniques such as molecular beam epitaxy, as has been demonstrated for numerous other transition metal chalcogenides including (for example) MnSe , CrSe (), and MnTe (). Furthermore, HgSe, the end‐member of the 5 d ‐selenide series to which ReSe would belong, occurs naturally in the zincblende structure with a lattice parameter of 6.085 Å and can be grown by MBE on GaSb substrates ().…”
Section: Introductionmentioning
confidence: 99%